2012
DOI: 10.1037/a0024468
|View full text |Cite
|
Sign up to set email alerts
|

Childhood trauma, poverty, and adult victimization.

Abstract: Trauma exposure and revictimization have many serious personal and public health consequences. Both individual-level and community-level factors impact a person's risk of being victimized, and there are currently few studies examining both individual and community levels of analysis in the same study. The current study employs multilevel modeling to examine how community-level poverty interacts with individuals' trauma histories and dissociative symptoms to predict later victimization. In this study, a cross-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
17
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(21 citation statements)
references
References 28 publications
4
17
0
Order By: Relevance
“…Certainly, this might quickly change if the same individual is detained in a special populations unit that privileges men who have sex with men. Intersectionality also explores how different levels of a social framework influence individuals experiences, including the intrapersonal level (e.g., internalized racism) (Mossakowski, 2003), the interpersonal level (e.g., bias,discrimination) (Kessler, Mickelson, & Williams, 1999), the contextual level (e.g., societal victimization such as hate crimes) (Klest, 2012), and the macro-level, where structural inequalities (e.g., education, income distribution). The study of intersectionality within institutions has also been examined including health-care contexts and how patients and providers both view and are viewed within health care institutions (Peek et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Certainly, this might quickly change if the same individual is detained in a special populations unit that privileges men who have sex with men. Intersectionality also explores how different levels of a social framework influence individuals experiences, including the intrapersonal level (e.g., internalized racism) (Mossakowski, 2003), the interpersonal level (e.g., bias,discrimination) (Kessler, Mickelson, & Williams, 1999), the contextual level (e.g., societal victimization such as hate crimes) (Klest, 2012), and the macro-level, where structural inequalities (e.g., education, income distribution). The study of intersectionality within institutions has also been examined including health-care contexts and how patients and providers both view and are viewed within health care institutions (Peek et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Experiencing severe victimizations could prevent someone from working, which might have a direct effect on income. Ultimately, such an individual might end up living in a high-poverty community, which in turn further promotes victimizations (Klest, 2012). Thus, a low income as well as experiencing trauma could create an environment that promotes poorer health and further traumatic experiences.…”
Section: Discussionmentioning
confidence: 98%
“…Another pathway to poorer health might come from the increased risk of financial and employment difficulties trauma survivors experience. Research has indicated that those who experience both childhood and adult trauma are more likely to be living in poverty (Klest, 2012;Zielinski, 2009), which could lead to poorer access to health care services due to lack of financial stability. Trauma might also affect health by affecting the survivor's relationships with others.…”
Section: Pathways Between Trauma and Healthmentioning
confidence: 99%
“…[43][44][45][46] For example, an African-American bisexual man may inhabit a different social position as a part of a community coalition to address HIV than while at work in the police department. Intersectionality also explores how different levels of a social framework influence individuals experiences, including the intrapersonal level (e.g., internalized racism), 47 the interpersonal level (e.g., bias, discrimination), 48 the contextual level (e.g., societal victimization such as hate crimes), 49 and the macro-level, where structural inequalities (e.g., education, income distribution) exist. 12 Intersectionality highlights how persons with multiple disadvantages can have interactive effects on their health and well-being.…”
Section: Applying Intersectionality To Health Disparitiesmentioning
confidence: 99%